Mediating role of sports team reputation: The relationships between team brand association, satisfaction, and loyalty in professional Thai football league - Suchao-in, Kanoknan; Gulthawatvichai, Sarist; Chatpunyakul, Chatchai (Kasetsart Journal of Social Sciences, 2021)
Past research on team brand association tended to focus on specific attributes in the spectator’s mind, linked to the team brand’s image, without taking sports team reputation into consideration. Sports team reputation is the collective perception by individuals who store their experiences or other forms of communication with the sports team, over time. Sports team reputation has been shown to have a strong influence on spectator’s experience, attitude, and behaviour. However, the relationship between brand association and reputation has not been established in sports marketing context. This study aims to examine the direct and the mediating effects of sports team reputation on the relationship between team brand association, satisfaction, and loyalty. Survey questionnaires were distributed to spectators who physically attended home games in professional Thai football league in 2017 (N = 1,600). The results suggest that sports team reputation can be improved by focusing on team brand association while satisfaction and loyalty can be enhanced by increasing sports team reputation. Sports team reputation plays a mediating role in the causal relationship between team brand association, satisfaction and loyalty in professional Thai football league. The highlight of this study comes from revealing sports team reputation as an outcome of a communication process by which individuals develop an emotional reaction and perception to actions associated with a sports team. These findings can be advantageous to managers who are involved in the reputation management process as they try to maintain their existing spectator base and to encourage new spectators.